PENYULUHAN MENGENAI KESEHATAN REPRODUKSI REMAJA KEPADA SANTRI PUTRA DAN PUTRI DARUL ARQAM MUHAMMADIYAH GARUT - Esa Risi Suazini; Lina Humaeroh; Fitri Hanriyani; Rosita Alvia (Jurnal Pengabdian Masyarakat DEDIKASI, 2020)
World Health Organization (WHO) 2014, informed that the proportion of adolescents is around 18%, or around 1.2 billion. (WHO, 2014) The results of the 2010 population census in Indonesia were 43.5 million, this number if proportioned the same, around 18%. Of this 43.5 million, only 20% of adolescents are not dating. They dated from <11 years of age. Teenagers mostly started dating aged 15-17 years, which is almost 50%. Pre-marital sex behavior occurs mostly at the age of 20-24 years, this behavior is more than 3 times that of young men. (Ministry of Health, Republic of Indonesia, 2017). Premarital sex has risks and bad effects, the risks that have to be faced with unwanted pregnancy (KtD), early pregnancy, abortion and transmission of sexually transmitted infections (STIs). an average of 25%. Very ironic, from 25% the highestknowledge is 60.8%, namely knowing that HIV-AIDS transmission can be reduced by using condoms. (Ministry of Health of the Republic of Indonesia, 2017). Health care for adolescents in Garut has not been running optimally. (Esa Risi Suazini, 2020). This condition shows that teenagers' exposure to health information is still low and has an impact on adolescent health knowledge which is also low. Based on the explanation above, it is very necessary to make efforts to increase adolescent knowledge about their reproductive health. The purpose of this community service is to disseminate adolescent reproductive information, increase adolescent knowledge about the correct adolescent reproductive health and shape healthy reproductive attitudes and behaviors in adolescents. The conclusion regarding the results of the dissemination of reproductive health information to adolescents, namely adolescents really need correct information about reproductive health. and adolescents have a positive attitude to always take care of their reproductive organs. After knowing the bad effects of sexual deviance, adolescents have a negative attitude towards sexual deviance. Our hope is that teenagers will survive to always avoid sexual deviant acts